2001
DOI: 10.2172/801196
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Rate of Formation of Hydroceramic Waste Forms made with INEEL Calcined Wastes

Abstract: iii Executive SummaryA "hydroceramic" nuclear waste form, developed especially to address the immobilization of the reprocessing wastes from the Idaho National Engineering and Environmental Laboratory, has been demonstrated to possess superior chemical and mechanincal properties. Furthermore, the processing requirements of hydroceramic waste forms are simple, less costly and offer greater safety to INEEL personnel than other waste form preparation systems.The objective of this research was two fold. The initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…64,65 Zeolites also form when metakaolin (Al 2 O 3 Á2SiO 2 ) or amorphous/glassy fly ash (0.74Al 2 O 3 Á2.40SiO 2 ) is reacted with excess NaOH during geopolymerization [73][74][75] and/or during hydroceramic formation. [76][77][78][79][80] According to a compilation by Barrer, 55 the zeolite analcime has been made from aluminous glass plus Na 2 SiO 3 and NaOH at 180-190°C, from NaAlO 2 and Na 2 SiO 3 at 180°C, from kaolin and Na 2 SiO 3 at 200-220°C, and from Al 2 O 3 plus 3-4 moles SiO 2 and Na 2 CO 3 at 190-200°C. Zeolites from synthetic sodic rich glasses with variable SiO 2 /Al 2 O 3 or Na 2 O/Al 2 O 3 and natural analog glasses have been studied in excess NaOH and found to form Zeoite A, Na-P zeolite, analcime, basic sodalite and/or faujasite.…”
Section: Appendix 1 Tutorial On Zeolitization In Industrial Applicatimentioning
confidence: 99%
“…64,65 Zeolites also form when metakaolin (Al 2 O 3 Á2SiO 2 ) or amorphous/glassy fly ash (0.74Al 2 O 3 Á2.40SiO 2 ) is reacted with excess NaOH during geopolymerization [73][74][75] and/or during hydroceramic formation. [76][77][78][79][80] According to a compilation by Barrer, 55 the zeolite analcime has been made from aluminous glass plus Na 2 SiO 3 and NaOH at 180-190°C, from NaAlO 2 and Na 2 SiO 3 at 180°C, from kaolin and Na 2 SiO 3 at 200-220°C, and from Al 2 O 3 plus 3-4 moles SiO 2 and Na 2 CO 3 at 190-200°C. Zeolites from synthetic sodic rich glasses with variable SiO 2 /Al 2 O 3 or Na 2 O/Al 2 O 3 and natural analog glasses have been studied in excess NaOH and found to form Zeoite A, Na-P zeolite, analcime, basic sodalite and/or faujasite.…”
Section: Appendix 1 Tutorial On Zeolitization In Industrial Applicatimentioning
confidence: 99%
“…Hydroceramics are zeolite-like crystalline materials synthesized from aluminosilicates (e.g., metakaolin, vermiculite, fly ash, and slag) via the hydrothermal method in alkaline conditions at a mild reaction temperature (80–200 °C). , Hydroceramics prepared using metakaolin have lower compressive strength (<5 MPa), which could be significantly improved up to 40 MPa by introducing slag in the synthesis mixture (Al/Si molar ratio is varied from 1 to 0.77 by the addition of slag from 0 to 50 wt %). ,,, …”
Section: Types Of Waste Formsmentioning
confidence: 99%
“…Scheetz et al reported the rate of formation of hydroceramic waste forms with Idaho National Engineering and Environmental Laboratory (INEEL) calcined wastes. The authors investigated the synthesis, characterization, and hydration kinetics of hydroceramic waste forms as potential hosts for existing INEEL calcined HLW as functions of temperature and processing time.…”
Section: Types Of Waste Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…[144,145] Hydroceramic wasteforms have been made with Idaho National Laboratory's HLW calcine. [146]…”
Section: Hydroceramicsmentioning
confidence: 99%